Effect of Grinding Inner Surface on Biaxial Flexural Strength, Phase Analysis and Surface Roughness of Translucent Zirconia - Wongjirasawad, Chalisa; Paisankobrit, Vibul (Srinakharinwirot University Dental Journal (E-ISSN 2774-0811), 2023)
Objective: Zirconia is generally used in dentistry. Grinding zirconia is difficult because of the high value of its surface hardness. Therefore, specific burs for grinding zirconia were created. To receive proper marginal fit, sometimes grinding a high spot at the inner surface of zirconia fixed partial denture was needed. The objective was to assess the effect of grinding inner surface on biaxial flexural strength (BFS), phase analysis and surface roughness of translucent zirconia. Materials and Methods: Forty samples, disc-shaped translucent zirconia, were randomly divided into four groups. CT group: no grinding samples; MD group: samples were ground by medium-grit diamond burs; FD group: samples were ground by fine-grit diamond burs; and HS group: samples were ground by heatless stone burs. The burs in MD group were represented as widespread commonly used burs; meanwhile, the burs in FD and HS groups were specifically for grinding zirconia. All samples were ground for a half-minute. The BFS was tested by Universal testing machine and the results were evaluated using one-way analysis of variance Scheffé test were performed to compare BFS among the groups (p-value < 0.05) Results: The monoclinic phase were existed in all ground zirconia groups and the roughness was raised compared with the CT group. The BFS of FD and HS group were not statistically significant differences from the CT group (p-value > 0.05). However, a significant reduction of BFS was observed in the MD group in comparison with the CT group (p-value < 0.05). Conclusions: Clinical inner surface adjustment of translucent zirconia fixed partial dentures with specific burs (FD and HS group) had no significant reduction of the BFS. Conversely, the BFS was reduced significantly after translucent zirconia was ground by common diamond burs (MD group). > ว.ทันต.มศว ปีที่ 16 ฉบับที่ 1 พ.ศ. 2566 หน้า 50-61. > SWU Dent J. 2023;16(1): 50-61.